Factors associated with healing of artificial ulcer after endoscopic submucosal dissection with reference to Helicobacter pylori infection, CYP2C19 genotype, and tumor location: Multicenter randomized trial. Issue 2 (20th October 2015) - Yoshizawa, Yashiro; Sugimoto, Mitsushige; Sato, Yoshihiko; Sahara, Shu; Ichikawa, Hitomi; Kagami, Takuma; Hosoda, Yoshisuke; Kimata, Masaharu; Tamura, Satoshi; Kobayashi, Yousuke; Osawa, Satoshi; Sugimoto, Ken; et al.
Abstract : Background and Aim: Healing speed of peptic ulcer is affected by a number of factors, including Helicobacter pylori ( H. pylori ) infection and intragastric pH. Acid inhibition exerted by proton pump inhibitors differs by CYP2C19 genotype. Herein, we investigated whether healing speed of artificial ulcers formed after endoscopic submucosal dissection (ESD) was influenced by H. pylori infection, CYP2C19 genotype, or other factors. Methods: A total of 96 H. pylori ‐positive patients with gastric tumors scheduled for ESD were randomly assigned to receive eradication therapy for H. pylori before ESD (pre‐ESD eradication) ( n  = 44) or after (post‐ESD eradication) ( n  = 52). Patients received eradication therapy consisting of lansoprazole 30 mg, amoxicillin 750 mg, and clarithromycin 200 mg twice daily for 1 week. After ESD, lansoprazole 30 mg was given once daily for 8 weeks. Ulcer size was endoscopically measured on the next day and at 4 and 8 weeks after ESD. Results: Mean reduction rate of artificial ulcer area in the pre‐ESD eradication group was 94.7% ± 5.5% at 4 weeks, which was similar to that in the post‐ESD eradication group (94.7% ± 6.7%, P  = 0.987), irrespective of CYP2C19 genotype. In multivariate analyses, location of gastric tumor (middle and upper, odds ratio: 4.05, 95% CI: 1.620–10.230, P  = 0.003) was a factor for 97% reduction of artificial ulcer area at 4 weeks post‐ESD, but CYP2C19 genotype and H. pylori infection were not. Conclusion: Healing speed of ESD‐induced artificial ulcer was affected by tumor location, but not by time of H. pylori eradication, resected size, or CYP2C19 genotype.